الحركة العلمية في الدولة الرستمية 160 - 296 هـ/ 777 - 909 م - راشد, ريم محمود محمد (مجلة البيان العلمية المحكمة, 2025)
Keywords: Dynastie rustumide; Vie intellectuelle -- Rustumides

‏ملامح الحياة الثقافية والسياسية في الدولة الرستمية 160-296هـ/776-909م - الشيخ بالحاج, قاسم بن أحمد (دار امل, 2021)
Keywords: Vie intellectuelle -- Rustumides

Non-caliphal Rulers and Their Writings in the Islamic West (2nd–9th/8th–15th Centuries) - Fierro, Maribel (Rulers as Authors in the Islamic World, 2024)
Among the dynasties ruling in the Islamic West, the Idrisids, the Aghlabids, the Fatimids, the Zirids and the Andalusi Taifa kings wrote poetry, but not the Ibāḍī rulers from North Africa. In the Ibāḍī and Ṣufrī polities that were established in Berber-speaking contexts court poetry in Arabic seems to have been absent, while religious piety and learning were extolled. In other contexts, the ability to write poetry signalled a ruler’s distinction, acumen and knowledge. Such ability seems to have been taken for granted in the case of the Cordoban Umayyad emirs and later among the Taifa kings, except for those who were Ṣaqāliba (slaves of European origin). The Arab Taifa king of Seville al-Muʿtamid (r. 461–484/1068–1091) was a highly talented poet whose verses are still appreciated and studied today. The existence of Andalusi rulers who wrote poetry was one of the elements that certain Andalusi authors emphasized in order to prove the cultural superiority of ‘Arab’ al-Andalus over North African ‘Berberdom’, although some members of both the Almoravid and Almohad dynasties are mentioned as having written poetry in Arabic. Rulers in the Islamic West also wrote prose works dealing with the art of government, the loss of power, adab, geometry, bookbinding and astronomy, a variety of topics that is to be understood in each specific context as explained in the second section of this chapter. Finally, the case of authors who became rulers is analyzed: the poet Ibn ʿAmmār, the ʿAzafids of Ceuta, the mystics Ibn Qasī (d. 546/1151) and Ibn Aḥlā al-Anṣārī (d. 645/1247), and the Mahdī Ibn Tūmart (d. 524/1130).
Keywords: Vie intellectuelle -- Rustumides

دور المرأة الرستمية في الحياة الفكرية (من ق2ه إلى ق3ه/ من ق8 إلى ق9ه) - جلول, الهادي (الحياة, 2017)
Keywords: Vie intellectuelle -- Rustumides

الفكر‬ ‫وأعلامه‬ ‫بالمغرب‬ ‫الأوسط‬ ‫أيام‬ ‫بني‬ ‫رستم - النوري, نور الدين (الحوار المتوسطي, 2018)
Keywords: Vie intellectuelle -- Rustumides

حياة الحضارية في الجزائر الرستمية (م909-777/ هـ 296-260) - قرواز, فتيحة (جامعة حسيبة بن بوعلي, 2012)
Keywords: Vie intellectuelle -- Rustumides

دور المكتبات في نشر العلوم بالمغرب األوسط تيهرت الرستمية (2-3هـ/8-9م) وتلمسان الزيانية (8-9هـ .)م45-44 - بوساق, رحيمة (جامعة محمد بوضياف, 2018)
Keywords: Vie intellectuelle -- Rustumides

الحياة العلمية في الدولة الرستمية 160ه- 296ه - خامت, كهينة; حمداوي, سعاد (جامعة أكلي محند أولحاج, 2015)
Keywords: Vie intellectuelle -- Rustumides

الحياة العلمية للإباضية في عهد الدولة الرستمية 296-160 هـ - عمي سعيد, زينب بنت توفيق (جمعية التراث, 2019)
Keywords: Dynastie rustumide; Vie intellectuelle -- Rustumides

المعتزلة في الدولة الرستمية - أحمد, سلوى عبدالخالق علي (حوليات آداب عين شمس, 2008)
اهتمت الدراسة بتاريخ المعتزلة والدور الذى لعبته في الدولة الرستمية سياسياً واقتصاديا وفكرياً وإنهم لم كونوا مجرد فرقة كلامية عولت على العقل في تأسيسي علم التوحيد أو علم الكلام وحققوا إنجازات أخرى جد هامة خصوصا على الصعيد الثقافي إذا ناظر أصحاب المذاهب الأخرى وخصوصا الخوارج الأباضية وتفوقوا عليهم بدرجة جعلت المذهب الأباصي نفسه يتأثر بالاعتزال بدرجة أو بأخرى والمعتزلة كفرقة كلامية تميزت بإنتاج غزير في مجالات متعددة وقدموا دراسات جادة ومبتكرة وكان لهم دور محمود في نشر الإسلام ليس فقط بين البربر بل حتى في أفريقيا جنوب الصحراء من خلال نشاطهم التجاري مع تلك البلاد إلى جنوب اهتمامهم بوجود جيش قائم في أماكن متفرقة من المغرب الأوسط أما عن دورهم الاجتماعي عرف عنهم إقامة اعتبار للعريقة والعصبية والعنصرية وهو ما يتسق مع طبيعة البربر والمعتزلة كفرقة كلامية وإن تميزت أفكارها بالعديد من الجوانب الإيجابية، فيعاب عليهم غلوهم في الاعتقاد بخلق القران وتشددهم في فرض رأيهم على البسطاء من العامة. غير أن هذه الانتقادات لا تقلل من الأثر العظيم الذي خلفته المعتزلة في الفكر الإسلامي. فهي بحق ساعدت على تقدم علم الكلام وقدمت لنا فكرا عميقاً امتزج فيه الكلام بالفلسفة.
Keywords: Vie intellectuelle -- Rustumides